Adding Biomolecular Recognition Capability to 3D Printed Objects: 4D Printing. (2017) - Mandon, C.A.; Blum, L.J.; Marquette, C.A.
Abstract: 3D printing technologies will impact in a near future the biosensor community, both at the sensor prototyping level and the sensing layer organization level. The present study aimed at demonstrating the capacity of one 3D printing technique, the Digital Light Processing (DLP), to produce hydrogel sensing layers with 3D shapes unreachable using conventional molding procedures but still biosensing activity (4D printed objects). The first model of sensing layer was composed of a sequential enzymatic reaction (glucose oxidase and peroxidase) and the generated chemiluminescent reaction in the presence of glucose and luminol used as analytical signal. Highly complex objects ( fancifuball, puzzle pieces, 3D pixel, propellers, fluidic, multi-compartments ) with mono-, di- and tri-components configurations were achieved and the activity of the encapsulated enzymes demonstrated. The second model was a sandwich immunoassay protocol for the detection of Brain Natriuretic Peptide. Here, highly complex propeller shape sensing layers were produced and the recognition capability of the antibodies demonstrated.